Review on miniaturization and development trends of SiC devices - ZHANG Yuanlan; ZHANG Qingchun (机车电传动)
Electrical vehicles and photovoltaic applications played important roles in the development of SiC devices, and promoted the improvement of the SiC industry chain in China. The design and manufacturing are developing rapidly, and the device performance of several domestic manufacturers has reached or approached the international leading level of SiC commercial products. However, the high price of SiC based devices still limits their further penetration into the power market. The miniaturization of SiC chips can significantly reduce the chip cost and has become one of the effective ways to further accelerate the large-scale application of SiC technologies in the power field. The necessity of SiC device miniaturization was analyzed, feasible solutions were proposed, and the rapid progress of SiC technologies was summarized. The major challenges for SiC device miniaturization were revealed, and the prospective development opportunities and future of SiC devices were described to provide a reference for further development of SiC power technologies.